(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Panduroga is a condition where in Pitta Pradhana Tridoshas affect the Dhathus causing deterioration of Varna and Bala, leading to Twak Vaivarnyatha or Pandutha. In present day medical science, symptoms of Pandu are alike to that of anaemia. Anemia is a condition presenting with a depletion of hemoglobin concentration below normal values, or Hematocrit or Red blood cells in the blood. On an average, about 30% or nearly one third of world’s population is claimed to be affected by anemia because of numerous causes. In India prevalence is extremely high compared to world prevalence, close to 51%. Nutritional macrocytic anemia (NMA) in prevailing population and in pregnancy, commonly seen in India, most likely represents combined deficiency of iron, folic acid and vitamin B12. A 45 years old female presented with complaints of Panduta (Pallor of skin), Daurbalya (weakness), Aruchi (loss of appetite), Padashopha (pedal oedema), Pindikodweshtana (leg cramps), Shrama Shwasa (exertional dyspnoea) and Hriddrava (palpitation) with haemoglobin concentration 3.7gm% visited OPD of SJIIM, GAMC, Bengaluru. Initially she was started with oral medications followed by admission to in-patient ward on the succeeding visit. The present case study is intended to understand the accuracy of multimodal Ayurvedic approach consisting of oral medications and Matra Basti with Dadimadya Ghrita, in the management of Panduroga and is found to be effective in overcoming Vataja Pandu